Targeting Inflammation and Downstream Protein Metabolism in Sarcopenia: A Brief Up-Dated Description of Concurrent Exercise and Leucine-Based Multimodal Intervention - Xia, Zhi; Cholewa, Jason; Zhao, Yan; Shang, Hua-Yu; Yang, Yue-Qin; Araújo Pessôa, Kassiana; Su, Quan-Sheng; Lima-Soares, Fernanda; Zanchi, Nelo Eidy (Frontiers in Physiology, 2017)
Sarcopenia is defined as the progressive loss of muscle mass with age, and poses a serious threat to the physiological and psychological health of the elderly population with consequential economic and social burdens. Chronic low-grade inflammation plays a central role in the development of sarcopenia such that it alters cellular protein metabolism to favor proteolysis over synthesis, and thereby accelerates muscular atrophy. The purpose of this review is to highlight how exercise and nutrition intervention strategies can attenuate or treat sarcopenia. Resistance exercise increases not only muscle mass but also muscle strength, while aerobic exercise is able to ameliorate the age-related metabolic disorders. Concurrent exercise training integrates the advantages of both aerobic and resistance exercise, and may exert a significant synergistic effect in the aging organism. Higher protein intakes rich in the amino acid leucine appear to restore skeletal muscle protein metabolism balance by rescuing protein synthesis in older adults. There is good reason to believe that a multimodal treatment, a combination of exercise and increased leucine consumption in the diet, can combat some of the muscle loss associated with aging. Future research is needed to consolidate these findings to humans, and to further clarify to what extent and by which mechanisms protein metabolism might be directly involved in sarcopenia pathogenesis and the multimodal treatment responses.